Milk fatty acid profile from grazing buffaloes fed a blend of soybean and linseed oils - Gagliostro, Gerardo Antonio (2015)
The aim of the study was to examine the changes in milk fatty acid (FA) profile of grazing buffaloes fed either a low (L, 276 g/d) or a high (H, 572 g/d) doses of a blend (70:30, wt/wt) of soybean and linseed oils. Fourteen multiparous Mediterranean buffaloes grazing a native pasture were fed 4 kg/day of a commercial concentrate containing no supplemental oil over a pre-experimental period of ten days. The baseline milk production and composition and milk FA profile was measured over the last three days. After this pre-experimental period, the animals received the same concentrate added with either the L or H oil doses for 26 additional days. Milk yield (g/animal/day) did not differ at the start (1776 ± 522 and 1662 ± 291 for L and H, respectively, P<0.622) or at the end of the trial (4590 ± 991 and 4847 ± 447 in L and H, respectively, P<0.543). Baseline milk fat content (g/kg) averaged 77.1 (±20.5) in L and 74.3 (±9.9) in H (P<0.10) and was reduced (P<0.031) to 60.7 (±23.6) and 49.4 (±11.2) (P<0.0031) respectively after L and H with no differences between treatments (P<0.277). Baseline milk protein content (L=43.2 ± 3.4 and H= 44.3 ± 6.9 g/kg) increased after oil supplementation (P<0.0001) in both L (73.2 ± 6.0 g/kg) and H (68.4 ± 4.9 g/kg) without differences between oil doses (P<0.123). Milk fat content of 14:0 decreased after oil supplementation only in H treatment (5.29 to 4.03, P<0.007) whereas that of 16:0 was reduced (P<0.001) at both L (24.49 to 19.75 g/100g FA) and H (25.92 to 19.17 g/100g FA) doses. The reduction of total content of 12:0 to 16:0 was higher (P<0.052) in H (32.02 to 23.93 g/100 g FA) than L (30.17 to 25.45 g/100g FA). Vaccenic acid content increased (P<0.001) from 5.70 to 13.24 g/100g FA in L and from 5.25 to 16.77 in H resulting higher in H treatment (P<0.001). Baseline rumenic acid was sharply increased (P<0.001) in L (1.80 to 4.09 g/100g FA, +127%) and H (1.60 to 4.61 g/100g FA, +187%) with no differences between L and H (P<0.19). Overall, these results indicate a pronounced improvement in the nutritional value of milk fat from grazing buffaloes fed little amounts (0.276 g/day) of a blend of soybean and linseed oils.